Land Degradation and Option of Practical Conservation Concepts in Manna Watershed Bengkulu Indonesia - Muhammad Faiz Barchia; Khairul Amri; Renra Apriantoni (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2018)
Watershed overcoming deteriorates in its function was indicated by increasing soil erosion and land degradation. The research aims were to determine and map critical land degradation levels and to chose options of practical conservation concepts in Manna watershed. The Manna watershed lays on 102°51'38.2